The relationship between human capital and firm value: Evidence from Indian firms - Garima Sisodia; Nemiraja Jadiyappa; Anto Joseph (Cogent Economics & Finance, 2021)
The purpose of this paper is to investigate whether human capital affects firm value by following a positive methodological approach. According to the clas- sical theory of economic growth, the output of a country depends on its human and physical capital. At the micro-level, the same theory holds true for firm output. Thus, the human capital of a firm should play a significant role in firm performance and therefore firm valuation. Our results show a positive relationship between human capital and firm value. Human capital creates value; first, by better utilization of current growth opportunities; second, by creating future growth opportunities, and lastly, by reducing the volatility associated with the firm growth rate. Also, we test the size effect on the relationship between human capital and firm value and do not find any differential impact.
Keywords: 330; firm growth; firm valuation; firm value; firm volatility; human capital